All the Muslims Fit to Print: Racial Frames as Mechanisms of Muslim Ethnoracial Formation in the New York Times from 1992 to 2010. Issue 4 (October 2020) - Yazdiha, Hajar
A generative turn in scholarship examines the institutional and political dimensions of Islamophobia, conceptualizing Muslim representations as a mechanism of ethnoracial formation in which the media is one such site of racialization. Moments of great political and cultural transformation can motivate and activate these racial projects, generating racialized representations that attach racial meaning to bodies. Much of the research on Muslim representations in news media centers on this very question: did the attacks of 9/11 usher in a new racial project? Previous studies offer competing hypotheses. Bridging social movement and communication theories with a theory of ethnoracial formation, the author develops an approach for evaluating racial framing processes through a comparison of diagnostic, prognostic, and motivational frames. The author applies this approach using computational text analysis techniques to examine latent shifts in the racial framing of Muslims in the New York Times in the decade before and after 9/11. The author finds evidence of increasingly racialized, but more complex, representations of Muslims in the decade after 9/11 in which diagnostic frames evolve from locating social problems in states and institutions to locating social problems in Muslim bodies. Prognostic frames shift from institutional reforms to those targeting group pathology. The author argues that excavating the latent mechanisms of racial projects helps us better understand the dynamic and ongoing processes of ethnoracial formation.